Determination of radon concentration in the imported tea in Al-Diwaniyah Governorate markets, Iraq using nuclear track detector LR-115 - Abbas A. Sweaf; Osamah N. Oudah (Caspian Journal of Environmental Sciences)
Radon concentration was determined in eleven different imported samples of tea that commonly use, collected from Al-Diwaniyah Governorate local markets in Iraq, using the SSNTD RL-115 detector. The results showed that the radon concentration differed in different tea types based on the origin of the tea trademark, where Cihan tea exhibited the highest radon concentration of 55.53 Bq m-3, while Balabel tea displayed the lowest value of 21.65 Bq/m3. These results indicate that radon concentrations were within safe limits for the consumer compared to the limits set by the (ICRP) 200 Bq m-3. This study will contribute to covering radiation studies on tea due to the proliferation of trademarks and insufficient studies on it.